Information Technology Governance Analysis Using the COBIT 2019 Framework at PT. Daya Adicipta Wisesa - Ramadhana, Rizky; Izaac, Bryan Vallentino; Tangka, George William; Mambu, Joe Yuan (SEULANGA SYSTEM PUBLISHER, 2023)
Information Technology can determine competitiveness and the ability to improve performace, as well as enhance effectiveness and efficienc for businesses, IT Governance can be considered successful when it aligns with organizational goals and the implementation for IT itself. Therefore, it is necessary to evaluate its maturity level. COBIT 2019 is one of the audit frameworks that can be used to control the Governance of information technology. PT. Daya Adicipta Wisesa is the subject of this research, with the aim of determining whether the implemented IT Governance has the desired Capability Level and to indentify the level of gaps in IT Governance based on the COBIT 2019 framework. Ater analyzing the 11 design factors of COBIT 2019, seven priority onjectives were found to have a target capability level 4, which is 80% namely APO13, BAI04, DSS01, DSS02, DSS03, DSS04, and DSS05. Then, the capability level calculation was conducted, and the priority onbjectives were determined as follows: APO13 achieved capability level 5, BAI03 achieved capability level 4, DSS01 achieved capability level 5, DSS02 achieved capability level 5, DSS03 achieved capability level 4, DSS04 achieved capability level 5, and DSS05 acvieved capability level 4, with a rating of fully achieved for the process activity category.